Peran Lumbrokinase pada Tata Laksana Stroke Iskemik - Marcellinus Michael Leonard Mardiono (Cermin Dunia Kedokteran, 2024)
Stroke is a major cause of disability and cognitive impairment, accounting for 5.2% deaths worldwide. Antiplatelets and anticoagulants have been widely used as prevention of recurrent stroke. Recently, lumbrokinase has been used in stroke and other cardiovascular patients, but further research is needed.